PWE-048 Performance of simple algorithm tests for the detection of fibrosis in non-alcoholic fatty liver disease. (23rd September 2015) - Miller, M; Jafferbhoy, H; Walsh, S; Dillon, J
Abstract : Aim: The aim of this study was to assess the performance of several simple algorithm tests for the detection of advanced fibrosis in NAFLD. Introduction: NAFLD is an increasingly common clinical entity and represents a significant burden in both primary and specialist care settings. Histological evaluation remains the gold standard investigative tool, although there is an increasing need for non-invasive assessment and categorisation. Several simple algorithm tests, utilising both simple biochemical and anthropological measurements have been designed to detect severe forms of fatty liver. This is an attractive proposition especially in the triage of patients either by the Primary care physician or the hepatologist who are confident of the diagnoses of NAFLD in their patients but would like to stratify them further between simple steatosis and steatohepatitis with fibrosis. Methods: We retrospectively applied seven scoring algorithms to 42 patients with biopsy proven NAFLD. All patients had negative liver screens and consumed <21 units of alcohol per week for men and 14 units per week for women. All biopsies were reviewed by an experienced hepatopathologist and the NAS scoring system applied, as well as the associated fibrosis grade. Results: Please see Abstract 048 . Where the test correctly predicted the presence of non-advanced disease, we assigned that patient as a potentially avoidable biopsy. Conclusion: Scoring systems employing routinely available clinical and biochemical markers are useful in the detection of advanced fibrosis in NAFLD. Simple scoring systems (AST/Plt, AST/ALT) perform as well as more complex algorithms (NAFLD-f). Application of simple scoring systems may reduce the number of biopsy performed.